2023
DOI: 10.1111/bph.16040
|View full text |Cite
|
Sign up to set email alerts
|

Biased GLP‐2 agonist with strong G protein‐coupling but impaired arrestin recruitment and receptor desensitization enhances intestinal growth in mice

Abstract: Background and Purpose Glucagon‐like peptide‐2 (GLP‐2) is secreted postprandially by enteroendocrine L‐cells and stimulates growth of the gut and bone. One GLP‐2 analogue is approved for short bowel syndrome (SBS). To improve therapeutic efficacy, we developed biased GLP‐2 receptor (GLP‐2R) agonists through N‐terminal modifications. Experimental Approach Variants with Ala and Trp substitutions of the first seven positions of GLP‐2(1‐33) were studied in vitro for affinity, G protein activation (cAMP accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The affinity trend differs from that previously observed for GLP-1­(7-36) variants with the nLuc-GLP-1R . In the GLP-2-NH 2 series, Gly4 → l -Ala had no effect on receptor affinity (consistent with findings of Gabe et al), and Gly4 → d -Ala caused only a small decline in affinity. In contrast, substantial GLP-1R affinity declines were previously observed for the Gly10 → l -Ala and Gly10 → d -Ala replacements in GLP-1­(7-36) .…”
Section: Resultsmentioning
confidence: 82%
“…The affinity trend differs from that previously observed for GLP-1­(7-36) variants with the nLuc-GLP-1R . In the GLP-2-NH 2 series, Gly4 → l -Ala had no effect on receptor affinity (consistent with findings of Gabe et al), and Gly4 → d -Ala caused only a small decline in affinity. In contrast, substantial GLP-1R affinity declines were previously observed for the Gly10 → l -Ala and Gly10 → d -Ala replacements in GLP-1­(7-36) .…”
Section: Resultsmentioning
confidence: 82%
“…The enhancement in the p-AKT levels induced for the d -GLP-2 analogues could be explained by the GLP-2R’s more prolonged activation, given that the d -GLP-2 analogs induce a lower β-arrestin recruitment (Figure D). A recent study showed that biased GLP-2 agonists, with strong G protein-coupling but impaired β-arrestin recruitment and receptor desensitization, enhance intestinal growth in mice . These authors also found that the GLP-2R could be internalized without β-arrestins but with lower efficiency and speed than with the presence of β-arrestins .…”
Section: Discussionmentioning
confidence: 99%
“…32 These authors also found that the GLP-2R could be internalized without β-arrestins but with lower efficiency and speed than with the presence of β-arrestins. 32 Arrestins are considered to be the central regulators of GPCR endocytosis because they bind to both phosphorylated receptors and adaptor protein 2 (AP-2) or clathrin, attracting receptors to clathrin-coated pits to promote internalization. 33 activation of the GLP-2R compensates for the lower levels of cAMP induced by the D-GLP-2 analogues, making the D-GLP-2 analogues induce similar GFP expression levels as L-GLP-2.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations did not reveal any significant correlation between the use of GLP-1R agonists and changes in areal bone mineral density (aBMD), a measure of bone density in specific body areas [30]. Moreover, the administration of GLP-1R agonists did not appear to affect the risk of bone fractures [31,32].…”
Section: The Impact Of Glp-1 On Bone Remodelingmentioning
confidence: 90%